Results from a survey in healthy blood donors in South Eastern Italy indicate that we are far away from herd immunity to SARS‐CoV‐2 - Fiore, Josè Ramòn; Centra, Michele; De Carlo, Armando; Granato, Tommaso; Rosa, Annamaria; Sarno, Michelina; De Feo, Lucia; Di Stefano, Mariantonietta; Errico, Maria D'; Caputo, Sergio Lo; De Nittis, Rosella; Arena, Fabio; et al. (Journal of medical virology, 2021)
Here we present results from a survey on anti‐severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) seroprevalence in healthy blood donors from a low incidence coronavirus disease 2019 area (Apulia region, South Eastern Italy). Among 904 subjects tested, only in nine cases (0.99%) antibodies against SARS‐CoV‐2 were demonstrated. All the nine seropositive patients were negative for the research of viral RNA by reverse transcription polymerase chain reaction in nasopharyngeal swabs. These data, along with those recently reported from other countries, clearly show that we are very far from herd immunity and that the containment measures are at the moment the only realistic instrument we have to slow the spread of the pandemic. Highlights Seroprevalence for SARS‐CoV‐2 antibodies was studied in group of 904 healthy blood donors from South Eastern Italy. Antibodies were detected only in nine (0.99%) cases. All the subjects were negative for viral RNA in nasopharyngeal swabs. Herd immunity to the virus is far away to reach and is probably not a viable option to contain the spread of the pandemic